2007
DOI: 10.1177/2345678906292238
|View full text |Cite
|
Sign up to set email alerts
|

Social Influences on Fertility

Abstract: This article uses a mixed methods design to investigate the effects of social influence on family formation in a sample of eastern and western German young adults at an early stage of their family formation. Theoretical propositions on the importance of informal interaction for fertility and family behavior are still rarely supported by systematic empirical evidence. Major problems are the correct identificationof salient relationships and the comparability of social networks across population subgroups. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(9 citation statements)
references
References 27 publications
(29 reference statements)
0
9
0
Order By: Relevance
“…Second, compared to higher educated mothers, lower educated mothers more often lack social, economic, and personal resources that help cope with parenting stress [40,41], which in turn may strengthen the chain of risk factors resulting in weight gain. In Germany, protective resources are strongly stratified by education [42,43], suggesting that lower educated women are more vulnerable to the effects of motherhood on weight gain.…”
Section: Education Motherhood and Weight Gain In The German Contextmentioning
confidence: 99%
“…Second, compared to higher educated mothers, lower educated mothers more often lack social, economic, and personal resources that help cope with parenting stress [40,41], which in turn may strengthen the chain of risk factors resulting in weight gain. In Germany, protective resources are strongly stratified by education [42,43], suggesting that lower educated women are more vulnerable to the effects of motherhood on weight gain.…”
Section: Education Motherhood and Weight Gain In The German Contextmentioning
confidence: 99%
“…Although additional empirical research has recently emerged, it remains limited due to the lack of suitable network data and the complexity of the analysis required to identify social interaction effects and disentangle them from confounding effects. Until now, next to the qualitative work of Bernardi and colleagues (e.g., Bernardi, 2003;Bernardi et al, 2007;Keim et al, 2009), which provided relevant insights into how social influence and learning operate to impact fertility choices in advanced societies, some recent studies adopted a quantitative approach to examining fertility outcomes. They empirically demonstrated that social interactions among siblings (Kuziemko, 2006;Lyngstad & Prskawetz, 2010), co-workers (Ciliberto et al, 2010;Hensvik & Nilsson, 2010), friends (Balbo & Barban, 2014), and peers belonging to the same ethnic-religious group (Manski & Mayshar, 2003) shape an individual's fertility decisions.…”
Section: Introductionmentioning
confidence: 99%
“…Intergenerational fertility correlations can be found consistently in developed countries and are increasing over time [4][5][6]. Most social scientists have explained these fertility continuities in terms of values transmitted from parents to children [8, 17 -20].…”
Section: Introductionmentioning
confidence: 99%
“…This reduction in fertility, called the fertility transition, is well known and widely documented [1][2][3]. A slightly less well-known but related phenomenon is that the correlation between parent and child fertility has increased from insignificant levels prior to the fertility transition, to moderate and increasing levels in contemporary societies [4][5][6]. This correlation may be genetic, cultural or some combination of the two [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%